Manufacturing method of composite material
By using anionic emulsifiers and polysaccharides during the composite material manufacturing process, the uneven dispersion of cell fibers in thermoplastic resins is solved, and the physical properties of composite materials are significantly improved.
Patent Information
- Application Number
- JP2021112412
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-07-06
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2041-07-06
AI Technical Summary
When manufacturing composite materials containing cell fibers and thermoplastic resins, cell fibers are prone to be unevenly dispersed due to hydrogen bond aggregation, which makes it difficult to improve the strength of the composite material.
By mixing the thermoplastic resin monomer with anionic emulsifier in an aqueous solution, an aqueous resin emulsifier is formed; then the emulsion, polysaccharide with hydroxyl groups and polysaccharides with water boiling point higher than water is mixed with cell fibers, and the first full stirring is performed to uniformly disperse; then the aqueous solution is removed and the product is heated and dried, and finally a second heating stirring is performed to remove polysaccharides and disperse the cell fibers evenly.
High uniform dispersion of cell fibers in thermoplastic resins is achieved, and the physical properties of composite materials are significantly improved.
Smart Images

Figure 0007650572000003 
Figure 0007650572000004 
Figure 0007650572000005
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a method for producing a composite material. [Background technology]
[0002] Cellulose nanofibers (hereinafter sometimes referred to as "CNF"), which are made by defibrating natural cellulose into nano-sized fibers, are attracting attention, and it is expected that the development of advanced materials using these will lead to the effective use of biomass. For example, reinforced resin compositions with improved physical properties have been developed by compounding CNF with thermoplastic resins.
[0003] The reinforced resin composition is obtained by mixing CNF and a thermoplastic resin to prepare an emulsion, and then removing water from the emulsion. Patent Document 1 discloses such a technique.
[0004] Patent Document 1 discloses a method for producing a resin modifying additive, which comprises the steps of reacting an N-oxyl compound, an oxidizing agent, and a co-oxidizing agent with natural cellulose fibers, followed by a micronizing step using a disperser to prepare an emulsion containing the obtained cellulose nanofibers and / or derivatives of the cellulose nanofibers, resin particles, and a liquid medium, and then removing the liquid medium from the emulsion by drying. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Patent No. 5923370 Summary of the Invention [Problem to be solved by the invention]
[0006] Conventionally, in the process of removing water from an emulsion containing CNF and a thermoplastic resin, there was a problem that CNF aggregated due to hydrogen bonding, making it difficult to uniformly disperse CNF in a thermoplastic resin. When CNF aggregates, it is difficult to improve the strength of the resulting resin composition. In Patent Document 1, in order to suppress such aggregation of CNF, an N-oxyl compound is allowed to act on natural cellulose to introduce a carboxyl group into CNF. By introducing the carboxyl group, the CNFs electrostatically repel each other in the process of removing water, and aggregation is suppressed. However, there is room for improvement in the technology for suppressing aggregation of CNF and dispersing CNF with high uniformity in a thermoplastic resin.
[0007] Therefore, a main object of the present application is to provide a method for producing a composite material that can improve physical properties. [Means for solving the problem]
[0008] As one means for solving the above-mentioned problems, the present disclosure provides an aqueous resin emulsion preparation process in which a thermoplastic resin monomer and an anionic emulsifier are mixed in an aqueous dispersion medium to obtain an aqueous resin emulsion containing a thermoplastic resin; an aqueous dispersion preparation process in which the aqueous resin emulsion, cellulose nanofibers having a carboxyl group, and a polyhydric alcohol having a boiling point higher than that of water are mixed to obtain an aqueous dispersion; a first kneading process in which the aqueous dispersion is kneaded; a drying process in which the aqueous dispersion medium is removed from the aqueous dispersion kneaded in the first kneading process; and a second kneading step of kneading the thermoplastic resin monomer from the aqueous resin emulsion to remove the polyhydric alcohol, wherein in the aqueous resin emulsion preparation step, the content of the anionic emulsifier is 1 to 3% by weight when the content of the thermoplastic resin monomer is 100% by weight, and in the aqueous dispersion preparation step, the content of the cellulose nanofiber is 1 to 30% by weight when the content of the thermoplastic resin is 100% by weight, and the content of the polyhydric alcohol is 5 to 20 times the content of the cellulose nanofiber on a weight basis, and in the second kneading step, the heating temperature of the dried product is set to tan δThe present invention provides a method for producing a composite material, in which the temperature is within a range of ±15° C. from the minimum value that appears next to the first maximum value that appears on the curve when viewed from the low temperature side. Effect of the Invention
[0009] In the composite material produced according to the present disclosure, the thermoplastic resin and CNF are dispersed with high uniformity, and therefore, according to the present disclosure, a composite material with improved physical properties can be produced. [Brief description of the drawings]
[0010] [Figure 1] 1 is a flow chart of a method 10 for producing a composite material. [Diagram 2] 4A shows the results of measuring the storage modulus E' of polymethyl methacrylate, and 4B shows the results of measuring tan δ of polymethyl methacrylate. [Diagram 3] 1 shows photographs of composite materials of Examples 1 and 2 and Comparative Examples 3 to 6. [Figure 4] 1 shows the measurement results of dynamic viscoelasticity tests for Examples 1 to 3 and Comparative Examples 1 and 2. [Diagram 5] 1 shows the measurement results of dynamic viscoelasticity tests for Example 3 and Comparative Examples 1 to 2 and 9. [Figure 6] 1 shows optical microscope images (magnification x 200) of Examples 1 to 3 and Comparative Examples 5 to 7. [Figure 7] 1 shows SEM images of Examples 1 to 3 and Comparative Examples 5 to 7 (top: magnification x1000, bottom: magnification x50000). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] The method for producing a composite material according to the present disclosure will be described using a composite material production method 10 (hereinafter, sometimes referred to as "production method 10") which is one embodiment. FIG.
[0012] 1, the production method 10 includes an aqueous resin emulsion preparation step S1, an aqueous dispersion preparation step S2, a first kneading step S3, a drying step S4, and a second kneading step S5. Each step will be described below.
[0013] <Water-based resin emulsion preparation process S1> The aqueous resin emulsion preparation step S1 is a step of mixing a thermoplastic resin monomer and an anionic emulsifier in an aqueous dispersion medium to obtain an aqueous resin emulsion containing a thermoplastic resin. By mixing the thermoplastic resin monomer and the anionic emulsifier in the aqueous dispersion medium, the polymerization of the thermoplastic resin monomer is promoted, and an aqueous resin emulsion containing fine thermoplastic resin can be prepared.
[0014] As the aqueous dispersion medium, water is usually used. However, an organic solvent soluble in water may be mixed as desired. The organic solvent soluble in water is not particularly limited, but examples thereof include alcohols, ethers, and ketones. In addition, in the drying step S4, it is preferable to use an organic solvent having a boiling point lower than that of water, from the viewpoint of removing the dispersion medium. When an organic solvent is mixed into the dispersion medium, the content of water may be 50% by weight or more, 70% by weight or more, 90% by weight or more, 95% by weight or more, or 99% by weight or more based on the entire dispersion medium.
[0015] As the thermoplastic resin monomer, known thermoplastic resin monomers such as acrylic acid monomers, methacrylic acid monomers, and styrene monomers can be used. These may be used alone or in combination. Methacrylic acid monomers are preferred, and methyl methacrylate monomers are more preferred.
[0016] As the anionic emulsifier, known anionic emulsifiers such as sodium dodecyl sulfate, sodium stearyl sulfate, sodium alkylbenzene sulfonate, etc. can be used. These may be used alone or in combination.
[0017] In the aqueous resin emulsion preparation step S1, when the content of the thermoplastic resin monomer is 100% by weight, the content of the anionic emulsifier is 1 to 3% by weight. If the content of the anionic emulsifier is less than 1% by weight, it becomes difficult to prepare the aqueous resin emulsion. If the content of the anionic emulsifier exceeds 3% by weight, the manufactured composite material is easily plasticized. If the composite material is plasticized, the physical properties such as elasticity decrease.
[0018] The reason for using an anionic emulsifier in the aqueous resin emulsion preparation step S1 is that an emulsion of fine resin particles can be prepared by adding a small amount. Specifically, by polymerizing a thermoplastic resin monomer in the presence of an anionic emulsifier, an aqueous resin emulsion can be obtained in which the thermoplastic resin particles are dispersed in a stable primary particle state. In this way, the resulting resin particles are very fine, so that they are close to the size of the CNF. Therefore, in the aqueous dispersion preparation step S2 and thereafter, the affinity (miscibility) between the thermoplastic resin and the CNF increases, making it possible to disperse them uniformly. By dispersing the thermoplastic resin and the CNF with high uniformity, the physical properties of the composite material, such as elasticity, can be improved.
[0019] The average particle size of the thermoplastic resin in the aqueous resin emulsion may be 10 nm or more, 20 nm or more, or 100 nm or less. The average particle size of the thermoplastic resin can be obtained by measuring the particle sizes (Ferret diameters) of, for example, 10 or more thermoplastic resin particles in an arbitrary region of the dried aqueous resin emulsion using a scanning electron microscope (SEM) and calculating the average value of these.
[0020] In addition, if the anionic emulsifier is replaced with a nonionic emulsifier, the resin particles in the emulsion tend to form secondary particles, which increases the tendency for gelation. According to the present inventors, in order to suppress gelation, it is necessary to add 8% by weight or more of a nonionic emulsifier. However, the composite material produced by such a method is plasticized, the glass transition temperature is lowered, the heat resistance is poor, and the material has low rigidity.
[0021] The mixing method is not particularly limited, and any known method can be used, for example, mixing and stirring using a mixer.
[0022] In the aqueous resin emulsion preparation step S1, additives necessary for the polymerization reaction of the monomers may be added as desired. For example, pH buffers such as sodium hydrogen sulfite and ammonium sulfite, and polymerization initiators such as sodium persulfate, potassium persulfate and ammonium persulfate may be added.
[0023] <Aqueous dispersion preparation process S2> The aqueous dispersion preparation step S2 is a step of mixing the aqueous resin emulsion prepared in the aqueous resin emulsion preparation step S1, cellulose nanofibers (CNF) having carboxyl groups, and a polyhydric alcohol having a boiling point higher than that of water to obtain an aqueous dispersion.
[0024] The CNF used is CNF having a carboxyl group. Such CNF is obtained by oxidizing the raw material natural cellulose with an N-oxyl compound such as TEMPO. The method of oxidizing natural cellulose with an N-oxyl compound is known. The CNF may be mixed with an aqueous resin emulsion and a polyhydric alcohol in a state dispersed in the above-mentioned aqueous dispersion medium (CNF dispersion). The fiber diameter of the CNF may be 3 to 10 nm, the fiber length may be 50 nm to 10 μm, and the aspect ratio (fiber length / fiber diameter) may be in the range of 20 to 350. The fiber diameter, fiber length, and aspect ratio of the CNF are obtained by placing the CNF dispersion on mica, drying it, and then measuring the CNF on the mica with an atomic force microscope (AFM). For example, 10 or more CNFs are measured. In this case, the fiber diameter and fiber length are the average values of the measurement results.
[0025] In the aqueous dispersion preparation step S2, when the content of the thermoplastic resin contained in the aqueous resin emulsion is taken as 100% by weight, the content of the cellulose nanofiber is set to be in the range of 1 to 30% by weight. In addition, in the aqueous dispersion preparation step S2, the content of the CNF may be 5% by weight or more, 10% by weight or more, or 20% by weight or less. If the content of the CNF is less than 1% by weight, the effect of improving the physical properties of the composite material becomes insufficient. If the content of the CNF is more than 30% by weight, the composite material tends to become brittle.
[0026] As the polyhydric alcohol, a polyhydric alcohol having a boiling point higher than that of water is used. By using a polyhydric alcohol having a boiling point higher than that of water, when the aqueous dispersion medium is removed from the aqueous dispersion in the drying step S4, the polyhydric alcohol is not removed and the polyhydric alcohol remains in the dried product, so that the aggregation of CNFs due to hydrogen bonds can be suppressed. By suppressing the aggregation of CNFs, the physical properties such as elasticity of the manufactured composite material can be improved. However, in the second kneading step S5, a polyhydric alcohol having a boiling point of 290° C. or less may be used to facilitate the removal of the polyhydric alcohol. Examples of such polyhydric alcohols include dihydric alcohols such as diethylene glycol and trihydric alcohols such as glycerin. In the aqueous dispersion preparation step S2, a single type of polyhydric alcohol may be used, or multiple types of polyhydric alcohols may be used.
[0027] In the aqueous dispersion preparation step S2, the polyhydric alcohol content is 5 to 20 times the CNF content by weight, and may be 10 to 20 times. If the polyhydric alcohol content is less than 5 times the CNF content, the effect of suppressing aggregation of cellulose nanofibers is reduced. If the polyhydric alcohol content is more than 20 times the cellulose nanofiber content, a large amount of polyhydric alcohol is squeezed out of the dried material in the second kneading step S5, making kneading difficult.
[0028] <1st kneading process S3> The first kneading step S3 is a step of kneading the aqueous dispersion obtained in the aqueous dispersion preparation step S2. The aqueous dispersion obtained in the aqueous dispersion preparation step S2 is a thickened liquid with high viscosity. The present inventors presume that this is because weak bonds are formed between the carboxyl groups or hydroxyl groups of the CNF and the anionic emulsifier in the resin particles via cations (e.g., sodium ions) derived from the anionic emulsifier, resulting in structural viscosity. Therefore, it is difficult to achieve a state in which the resin particles and the CNF are highly uniformly dispersed by simply mixing in the aqueous dispersion preparation step S2. Therefore, by kneading the aqueous dispersion in the first kneading step S3, a highly uniform dispersion state can be achieved.
[0029] The method for kneading the aqueous dispersion is not particularly limited, but examples thereof include rotation-revolution mixing and roll kneading.
[0030] Rotation and revolution mixing can be performed using a known rotation and revolution mixing device. The conditions of rotation and revolution mixing can be appropriately set so that the aqueous dispersion can be kneaded. For example, rotation is performed at 1,400 rpm and rotation at 700 rpm for 30 seconds, and then rotation is performed at 1,800 rpm and rotation at 54 rpm for 30 seconds.
[0031] The roll kneading can be carried out using a known open roll. The conditions for the roll kneading can be appropriately set so as to knead the aqueous dispersion. For example, in roll kneading, the number of rolls may be two or three. When there are two rolls, the roll speed ratio may be front roll / rear roll=20.0 rpm / 17.0 rpm, and the roll interval may be 0 to 0.5 mm or less. When there are three rolls, the roll speed ratio may be first roll / second roll / third roll=30 rpm / 90 rpm / 270 rpm=1 / 3 / 9, and the roll interval may be 0.3 mm. In addition, CNF can be defibrated by roll kneading.
[0032] In the first kneading step S3, the water-based dispersion may be kneaded once or multiple times. When kneading multiple times, different kneading methods may be combined.
[0033] <Drying process S4> The drying step S4 is a step of removing the aqueous dispersion medium from the aqueous dispersion liquid kneaded in the first kneading step S3. The method of removing the aqueous dispersion medium from the aqueous dispersion liquid is not particularly limited. For example, the aqueous dispersion medium may be dried at room temperature, or may be dried by heating. Usually, the aqueous dispersion medium is dried by heating. The heating temperature is set to a temperature at which the polyhydric alcohol is not removed. For example, it is 30°C or higher and 50°C or lower. The heating time is set to a time at which the aqueous solvent can be sufficiently removed. For example, it is 24 hours to 48 hours. When the aqueous dispersion medium is removed from the aqueous dispersion liquid, a gel-like dried product is obtained.
[0034] <Second kneading process S5> The second kneading step S5 is a step in which the dried product obtained in the drying step S4 is kneaded while being heated to remove the polyhydric alcohol. The drying step S4 aims to remove the aqueous solvent, and the polyhydric alcohol is not removed. In the drying step S4, if the temperature is simply raised to remove the polyhydric alcohol together with the aqueous solvent, a problem occurs in which the CNF aggregates. Therefore, in the second kneading step S5, the dried product is kneaded while being heated to defibrate the CNF and remove the polyhydric alcohol.
[0035] However, in the second kneading step S5, the polyhydric alcohol does not have to be completely removed from the dried product, but only needs to be almost completely removed. This can be confirmed by visual inspection. If the polyhydric alcohol is not completely removed, the kneaded product obtained after the second kneading step S5 may be further heated to completely remove the polyhydric alcohol. The heating method is, for example, heat treatment in an oven. From the viewpoint of suppressing deterioration of the CNF, heat treatment in a reduced pressure oven may be performed. The heating temperature may be 130 to 170°C. In the heat treatment in a reduced pressure oven, the pressure is not particularly limited, but may be, for example, vacuum (for example, -0.1 MPa or less).
[0036] The second kneading step S5 can be carried out using an apparatus for melting and molding the dried material, an open roll, an internal kneader, an extruder, an injection molding machine, or the like. It is preferable to use an open roll. When an open roll is used, the conditions for roll kneading are as follows. The number of rolls may be two or three. The roll interval may be more than 0 and 0.5 mm or less. When the number of rolls is two, the roll speed ratio may be 1.05 to 3.00, or may be 1.05 to 1.2.
[0037] In the second kneading step S5, the heating temperature of the dried material is determined based on the tan δ In the curve, the range is within ±15°C (minimum value -15°C to minimum value +15°C) from the minimum value that appears next to the first maximum value seen from the low temperature side. In other words, the "minimum value that appears next to the first maximum value seen from the low temperature side" is tan δ It is a minimum value that appears on the low temperature side and is on the high temperature side of the maximum value that appears on the low temperature side of the curve.
[0038] In this temperature range, the kneaded material has appropriate elasticity and viscosity, so that the thermoplastic resin can be largely deformed by the restoring force due to the elasticity of the thermoplastic resin, and the CNF moves largely due to the deformation, and the CNF is defibrated. This allows the resin particles and the CNF to be uniformly dispersed. If the heating temperature of the dried material in the second kneading step S5 is less than the minimum value -15°C, the resin becomes too hard for kneading. If the heating temperature of the dried material in the second kneading step S5 exceeds the minimum value +15°C, the elasticity of the thermoplastic resin decreases and the viscosity of the kneaded material increases, so that the shear force that defibrates the CNF decreases.
[0039] The heating temperature of the dried material can be obtained as follows. First, the aqueous dispersion medium is removed from the aqueous resin emulsion prepared in the aqueous resin emulsion preparation step S1 to obtain a thermoplastic resin. The method of removing the aqueous dispersion medium from the aqueous resin emulsion can be the same as that of the drying step S4 described above. Next, the obtained thermoplastic resin is molded by pressing or the like, and then cut into strips to obtain a test piece for dynamic viscoelasticity measurement. The size of the test piece may be such that dynamic viscoelasticity measurement can be performed. For example, the width is 4 mm, the length is 40 mm, and the thickness is 0.3 mm. Then, dynamic viscoelasticity measurement is performed. A known dynamic viscoelasticity tester can be used as the measuring device. For example, a dynamic viscoelasticity tester DMS6100 manufactured by Hitachi High-Tech Science Corporation can be used. The measurement method is performed based on JIS K7244, with the chuck distance set to 20 mm, the measurement temperature -50°C to 300°C, the temperature rise rate to 1.5°C, the dynamic strain to 0.05%, and the frequency set to 1 Hz. The obtained tan δ From the curve, the next minimum value after the first maximum value seen from the low temperature side is found. Finally, a temperature range of ±15°C around the minimum value is determined, that is, the heating temperature range of the drying material.
[0040] When polymethyl methacrylate is used as the thermoplastic resin, that is, when polymethyl methacrylate is used in the aqueous resin emulsion preparation step S1, the heating temperature of the dried material in the second kneading step S5 is in the range of 160° C. to 190° C. According to the present inventors, this temperature range is set so that the storage elastic modulus E' of polymethyl methacrylate is about 2 to 3 MPa, tan δ is about 0.2 or less. If the heating temperature is less than 160°C, the polymethacrylate resin becomes hard and is not suitable for kneading. If the heating temperature exceeds 190°C, the storage modulus E' of the polymethacrylate resin becomes 1 MPa or less, the elasticity decreases, the viscosity of the kneaded material increases, and the shear force that defibrates the CNF decreases.
[0041] For reference, Fig. 2(A) shows the storage modulus E' of polymethyl methacrylate, and Fig. 2(B) shows the tan δ The measurement results are shown in Table 1. The measurement method is as described above.
[0042] The kneaded product (composite material) obtained by the second kneading step S5 or heat-treated after the second kneading step S5 may then be molded. The molding method is not particularly limited, and known methods can be used. For example, vacuum press molding, injection molding, extrusion molding, etc. may be mentioned. In addition, molding may be performed using only the composite material, or it may be mixed with other resins and molded.
[0043] The composite material manufacturing method of the present disclosure has been described above using the composite material manufacturing method 10, which is one embodiment. In the composite material manufacturing method of the present disclosure, an anionic emulsifier is used to prepare an aqueous resin emulsion containing fine thermoplastic resin (particularly, polymethyl methacrylate), so that the affinity (miscibility) between the thermoplastic resin and CNF is high. In addition, by adding a polyhydric alcohol to the aqueous dispersion, it is possible to suppress the aggregation of CNF when removing the aqueous dispersion medium. Furthermore, in the first kneading step, the resin particles and CNF can be kneaded uniformly, and in the second kneading step, the CNF can be defibrated. These actions combine to disperse the thermoplastic resin and CNF with high uniformity, and improve the physical properties of the composite material, such as elasticity. EXAMPLES
[0044] The present disclosure will now be further described with reference to examples.
[0045] [Preparation of composite materials] Composite materials of Examples 1 to 14 and Comparative Examples 1 to 19 were prepared as follows. Tables 1 and 2 show the contents of the materials and the conditions of the kneading process.
[0046] <Example 1> (Water-based resin emulsion production process) Sodium hydrogen sulfite (Fujifilm Wako Pure Chemical Industries, Ltd., special grade reagent) 0.2 g was dissolved in 10 ml of pure water to prepare a sodium hydrogen sulfite aqueous solution. Sodium persulfate (Alfa Aesar, 97% reagent) 0.45 g was dissolved in 10 ml of pure water to prepare a sodium persulfate aqueous solution.
[0047] 200 g of pure water was placed in a 500 ml four-neck flask equipped with a stirrer and reflux device, and 1.5 g of anionic emulsifier sodium dodecyl sulfate (Wako First Grade Reagent, Fujifilm Wako Pure Chemical Industries, Ltd.) was added, and the mixture was stirred and dissolved while replacing with nitrogen gas. Next, 15 g of methyl methacrylate monomer (Wako Special Grade Reagent, Fujifilm Wako Pure Chemical Industries, Ltd.) and 2 ml of sodium hydrogen sulfite aqueous solution were added to the flask, and the temperature was raised to 70 ° C. while stirring at 250 rpm. After stirring for 30 minutes, 2 ml of sodium persulfate aqueous solution was added and stirred for another 30 minutes. Next, 60 g of methyl methacrylate monomer was dropped over 2 hours. In addition, 8 ml of sodium hydrogen sulfite and 8 ml of sodium persulfate were similarly dropped over 2 hours. Next, the temperature was raised to 75 ° C. and aged for 1 hour. After cooling to room temperature, the mixture was filtered through a 200 mesh to obtain an aqueous resin emulsion containing polymethyl methacrylate (PMMA).
[0048] (Aqueous dispersion preparation process) First, 15 g of water was added to 40 g of CNF aqueous dispersion (Cellenpia TC-01A, 1 wt.% manufactured by Nippon Paper Industries Co., Ltd.) (TEMPO oxidized CNF), diluted and mixed, and then 32 g of the aqueous resin emulsion (concentration 25.0%) obtained above and 4 g of diethylene glycol (special grade reagent manufactured by Kanto Chemical Co., Ltd.) (DEG) were added. At this time, when the PPMA in the aqueous resin emulsion was 100 wt.%, the CNF content was 5 wt.%, and the diethylene glycol content was 10 times the CNF content by weight. Next, the obtained mixture was stirred and mixed at a rotation speed of 20,000 rpm for 15 seconds using a juicer mixer (blender MX1200XTX manufactured by Waring) to obtain an aqueous dispersion.
[0049] <1st kneading process> The obtained aqueous dispersion was applied to a revolutionary mixer (Thinky Corporation, model number: Awatori Rentaro ARV-930WN Rentaro) and kneaded and defoamed. Specifically, the mixture was first rotated at 1,400 rpm and 700 rpm for 30 seconds, and then rotated at 1,800 rpm and 54 rpm for 30 seconds.
[0050] Next, roll mixing was performed using an open roll with three rolls. The roll gap was 0.3 mm, and the roll speed ratio was 1st roll / 2nd roll / 3rd roll = 30 rpm / 90 rpm / 270 rpm = 1 / 3 / 9. The aqueous dispersion was applied to the roll mixer twice.
[0051] <Drying process> The kneaded aqueous dispersion was transferred to a tray and dried for 36 hours in an oven at 40° C. After confirming that the water had been sufficiently removed, a gel-like dried product was obtained.
[0052] <Second kneading process> The obtained dried product was roll kneaded using an open roll with two rolls. The roll kneading was started under the condition of an initial temperature of 160°C to 170°C and a roll rotation speed (front roll 20 rpm, rear roll 17 rpm), and the roll gap was narrowed from 0.5 mm to 0.3 mm and 0.1 mm. As the DEG evaporated, the roll temperature was increased to 170°C to 190°C, and the kneading was continued until the evaporation of DEG was no longer visible. The obtained kneaded product was dried at 160°C for 24 hours using a reduced pressure oven to completely remove the DEG, and the composite material of Example 1 was obtained.
[0053] The obtained composite material was press molded at a temperature of 200° C. using a vacuum press machine to form a plate with a thickness of 0.3 mm.
[0054] <Examples 2 to 5> Composite materials of Examples 2 to 5 were produced in the same manner as in Example 1, except that in the aqueous dispersion production step, the ratio of PMMA to CNF was changed to the ratio shown in Table 1.
[0055] <Examples 6 to 7> The composite materials of Examples 6 and 7 were prepared in the same manner as in Example 2, except that in the aqueous dispersion preparation step, the DEG content relative to the CNF content was changed to the ratio shown in Table 1.
[0056] <Example 8> A composite material of Example 8 was produced in the same manner as in Example 2, except that roll kneading was omitted in the first kneading step.
[0057] <Example 9> A composite material of Example 9 was produced in the same manner as in Example 2, except that the rotation-revolution stirring was omitted in the first kneading step.
[0058] <Example 10> A composite material of Example 10 was produced in the same manner as in Example 2, except that in the first kneading step, roll kneading was performed using two rolls. The roll kneading was performed at room temperature, with the roll gap set to 0.2 mm and the speed ratio of the first roll / second roll set to 1.1 / 1.0.
[0059] <Example 11> The composite material of Example 11 was prepared in the same manner as in Example 3, except that in the aqueous dispersion preparation step, the type of polyhydric alcohol was changed from DEG to glycerin, and in the second kneading step, the kneaded material was dried at 170°C for 24 hours using a reduced pressure oven.
[0060] <Examples 12 to 13> Composite materials of Examples 12 and 13 were produced in the same manner as in Example 3, except that the content of sodium dodecyl sulfate was changed to the content in Table 1 in the aqueous resin emulsion production step.
[0061] <Example 14> The composite material of Example 14 was prepared in the same manner as in Example 3, except that in the aqueous resin emulsion preparation step, the type of anionic emulsifier was changed from sodium dodecyl sulfate to sodium stearyl sulfate.
[0062] <Comparative Example 1> As the PMMA resin, PMMA resin pellets (Parapet GH-S manufactured by Kuraray Co., Ltd.) were used and press molded at 170° C. to prepare the material of Comparative Example 1.
[0063] <Comparative Example 2> The water-based resin emulsion prepared in Example 1 was placed in an oven at 80° C. for 24 hours to remove moisture, and PMMA was obtained. The PMMA was then press molded at 220° C. to prepare the material of Comparative Example 2.
[0064] <Comparative Examples 3 to 4> Composite materials of Comparative Examples 3 and 4 were prepared in the same manner as in Examples 2 and 3, except that DEG was not added in the aqueous dispersion preparation step and the second kneading step was omitted.
[0065] <Comparative Examples 5 to 7> Composite materials of Comparative Examples 5 to 7 were prepared in the same manner as in Examples 1 to 3, except that DEG was not added in the aqueous dispersion preparation step.
[0066] <Comparative Example 8> The composite material of Comparative Example 8 was prepared in the same manner as in Example 3, except that the DEG content was changed to 30 times the CNF content in the aqueous dispersion preparation process.
[0067] <Comparative Example 9> The composite material of Comparative Example 9 was prepared in the same manner as in Example 1, except that the DEG content was changed to 10 times the CNF content in the aqueous dispersion preparation step.
[0068] <Comparative Example 10> A composite material of Comparative Example 10 was prepared in the same manner as in Example 1, except that in the aqueous dispersion preparation step, the content ratio of PMMA to CNF was changed to PMMA:CNF=100:35.
[0069] <Comparative Example 11> A composite material of Comparative Example 11 was produced in the same manner as in Example 3, except that the kneading temperature was changed to 220°C in the second kneading step.
[0070] <Comparative Examples 12 to 14> The composite materials of Comparative Examples 12 to 14 were prepared in the same manner as in Examples 1 to 3, except that in the aqueous dispersion preparation process, the type of CNF was changed from TEMPO-oxidized CNF to carboxymethylated CNF (manufactured by Nippon Paper Industries Co., Ltd.) (CM-CNF).
[0071] <Comparative Example 15> An attempt was made to prepare a composite material of Comparative Example 15 in the same manner as in Example 2, except that in the aqueous resin emulsion preparation process, the ratio of the content of sodium dodecyl sulfate to the content of methyl methacrylate monomer was changed to methyl methacrylate monomer:sodium dodecyl sulfate=100:0.6. However, the emulsion gelled during the polymerization, and a good emulsion could not be obtained, so that a composite material could not be prepared.
[0072] <Comparative Example 16> The composite material of Comparative Example 16 was prepared in the same manner as in Example 2, except that in the aqueous resin emulsion preparation process, the ratio of the content of sodium dodecyl sulfate to the content of methyl methacrylate monomer was changed to methyl methacrylate monomer:sodium dodecyl sulfate=100:4.
[0073] <Comparative Examples 17 to 19> The composite materials of Comparative Examples 17 to 19 were prepared in the same manner as in Examples 1 to 3, except that in the aqueous resin emulsion preparation process, the type of emulsifier was changed from an anionic emulsifier, sodium dodecyl sulfate, to a nonionic emulsifier, polyoxyalkylene alkyl ether (Sanyo Chemical Industries: Naroacty CL-400) (POAAE), and the content ratio of POAAE was changed to methyl methacrylate monomer:POAAE=100:8.
[0074] [evaluation] The following tests were carried out on the prepared composite material.
[0075] <Appearance Observation> The appearance of the composite materials was visually observed to evaluate the presence or absence of aggregation of CNFs, and the color tone was also evaluated for those with distinctive color tones. The results are shown in Tables 1 and 2. Photographs of the composite materials of Examples 1 and 2 and Comparative Examples 3 to 6 are shown in Figure 3.
[0076] <Tensile test> The composite material was cut into strips to obtain test pieces with a width of 4 mm, a length of 90 mm, and a thickness of 0.3 mm. The elastic modulus, maximum stress, and tensile elongation of the test pieces were measured using a tensile tester (Shimadzu Autograph AG-X) with a gauge length of 10 mm and a tensile speed of 2 mm / min. The results are shown in Tables 1 and 2.
[0077] <Dynamic viscoelasticity measurement (DMA measurement)> The composite material was cut into strips to obtain test pieces with a width of 4 mm, a length of 40 mm, and a thickness of 0.3 mm. Next, using a dynamic viscoelasticity tester (Hitachi High-Tech Science DMS6100), the following conditions were set based on JIS K7244: chuck tube distance 20 mm, measurement temperature -50°C to 300°C, heating rate 1.5°C, dynamic strain 0.05%, and frequency 1 Hz. The dynamic viscoelasticity (storage modulus E', loss modulus E'', loss tangent tan δ From the measurement results, the storage modulus E' (200°C) and loss tangent tan δ The peak value was calculated. The results are shown in Tables 1 and 2. The measurement results of Examples 1 to 3 and Comparative Examples 1 and 2 are shown in FIG. 4, and the measurement results of Example 3 and Comparative Examples 1 to 2 and 9 are shown in FIG.
[0078] <Measurement of linear expansion coefficient (TMA measurement)> The composite material was cut into strips to obtain test pieces with a width of 2 mm, a length of 20 mm, and a thickness of 0.3 mm. Next, a thermomechanical analysis tester (Hitachi High-Tech Science Corporation, TMA7100) was used to measure the linear expansion coefficient of the test pieces, setting the chuck tube distance to 10 mm, the measurement temperature to -30°C to 200°C, and the temperature rise rate to 3°C / min. The results are shown in Tables 1 and 2.
[0079] <Microscope observation> Observation was performed with an optical microscope and a scanning electron microscope (SEM) for the composite materials of Examples 1 to 3 and Comparative Examples 5 to 7. Optical microscope images (magnification: ×200) are shown in Fig. 6, and SEM images (upper: magnification: ×1000, lower: magnification: ×50000) are shown in Fig. 7.
[0080] [Table 1]
[0081] [Table 2]
[0082] [result] The elastic modulus was higher and the linear expansion coefficient was lower in Examples 1 to 14 than in Comparative Examples 1 and 2 (PMMA resin). Moreover, the results of Examples 1 to 14 show that the decrease in breaking elongation due to the addition of CNF was within an acceptable range.
[0083] In Comparative Examples 3 and 4, a large number of CNF aggregates were present, and the samples were very brittle, making it impossible to measure the physical properties.
[0084] In Comparative Examples 5 to 7, the aggregates of CNF were not noticeable by visual inspection. However, from the optical microscope images, the size of the aggregates was obviously larger than that of Examples 1 to 3, and the number of aggregates was also larger. In addition, from the SEM images, it was confirmed that Examples 1 to 3 had many smooth surfaces and high uniformity between the thermoplastic resin and CNF, but Comparative Examples 5 to 7 had a crown-shaped wave surface, and it could not be said that the uniformity between the thermoplastic resin and CNF was high. In terms of physical properties, Comparative Examples 5 to 7 had smaller breaking elongation and smaller maximum stress than Examples 1 to 3. This is thought to be because the aggregation of CNF could not be suppressed in the drying process due to the absence of DEG, and therefore many CNF aggregates were formed in the composite material, which resulted in a decrease in physical properties.
[0085] In Comparative Example 8, a large amount of DEG was squeezed out of the dried material in the second kneading step, causing the dried material to slip on the rolls and preventing proper kneading.
[0086] The effect of improving the physical properties by adding CNF was insufficient in Comparative Example 9. Specifically, the maximum stress and breaking elongation of Comparative Example 9 were smaller than those of Example 4, and the linear expansion coefficient was larger.
[0087] In Comparative Example 10, the amount of CNF was excessive, and the breaking elongation was lower than that in Example 5, and the product was brittle.
[0088] In Comparative Example 11, the increase in elastic modulus was small and the tensile elongation was small compared to Example 3. This is thought to be because the temperature condition in the second kneading step was as high as 220°C, which was in a range where elastic kneading was not sufficiently performed (fluid kneading), and therefore the defibration of CNF was insufficient.
[0089] In Comparative Examples 12 to 14, the CNF was changed to carboxylated CNF, so the increase in elastic modulus was small and almost no effect due to CNF was observed compared to Examples 1 to 3. Also, the decrease in linear expansion coefficient was small.
[0090] In Comparative Example 16, the ratio of the content of sodium dodecyl sulfate to the content of methyl methacrylate monomer was increased to 100:4 in the aqueous resin emulsion preparation process, so that the peak value of tan δ in the DMA measurement was 126°C, and the resin melted at 200°C or less. From this, it is estimated that plasticization of the resin occurred in Comparative Example 16. In addition, the linear expansion coefficient was large in Comparative Example 16, which is also considered to be due to the influence of plasticization of the resin.
[0091] In Comparative Examples 17 to 19, the anionic emulsifier was changed to a nonionic emulsifier, so that the storage modulus E' curve of the DMA measurement shifted to a lower temperature side by 15°C to 22°C, and the peak value of tan δ dropped to 111°C to 117°C. In addition, Comparative Examples 17 and 18 melted at 200°C or less. From this, it is estimated that significant plasticization of the resin occurred in Comparative Examples 17 to 19. In addition, Comparative Examples 17 to 19 had a large linear expansion coefficient, which is also considered to be due to the influence of plasticization of the resin.
Claims
[Claim 1] an aqueous resin emulsion preparation step of mixing a thermoplastic resin monomer and an anionic emulsifier in an aqueous dispersion medium, and emulsion-polymerizing the mixture to obtain a thermoplastic resin, and then obtaining an aqueous resin emulsion containing the thermoplastic resin; an aqueous dispersion preparation step of mixing the aqueous resin emulsion, cellulose nanofibers having a carboxyl group, and a polyhydric alcohol having a boiling point higher than that of water to obtain an aqueous dispersion; A first kneading step of kneading the aqueous dispersion; A drying step for removing the aqueous dispersion medium from the aqueous dispersion liquid kneaded in the first kneading step; A second kneading step of kneading the dried product obtained in the drying step while heating it to remove the polyhydric alcohol, In the aqueous resin emulsion preparation step, the content of the anionic emulsifier is 1 to 3% by weight when the content of the thermoplastic resin monomer is taken as 100% by weight, In the aqueous dispersion preparation step, the content of the cellulose nanofiber is 1 to 30% by weight when the content of the thermoplastic resin is taken as 100% by weight, and the content of the polyhydric alcohol is 5 to 20 times the content of the cellulose nanofiber on a weight basis; In the second kneading step, the heating temperature of the dried material is within a range of ±15° C. centered on the minimum value that appears next to the first maximum value that appears from the low temperature side in the tan δ curve obtained by dynamic viscoelasticity measurement of the thermoplastic resin. Manufacturing methods for composite materials.
Citation Information
Patent Citations
Making of adhesive label
JP1984023370A
Method for producing thermoplastic resin composition and thermoplastic resin composition
JP2016029169A
Method for producing fiber material, method for producing composite material, fiber material and composite material
JP2019173253A
Manufacturing method of composite resin composition
JP2020200361A